Nanopores - Ameen, Sadia; Shaheer Akhtar, M.; Shin, Hyung-Shik (IntechOpen, 2021)
The field of nanoporous materials has advanced significantly over the last two decades with new concepts and applications emerging all the time. This book is a comprehensive and easy-to-understand source of information on the latest developments in nanopore research. It is a collection of contributions from leading specialists in the subject that address topics such as synthetic methodologies, characterization techniques, and applications of nanopores. This book will appeal to a wide spectrum of readers, including students, professors, and professionals.